FRI0540 Evaluation of Nailfoldvideocapillaroscopy in Central Serous Chorioretinopathy. (15th July 2016) - Erol, M.K.; Balkarli, A.; Toslak, D.; Durmaz, D.; Dogan, B.; Baskan, E.; Altun, S.; Bulut, M.; Cobankara, V.
Abstract : Background: Nailfold videocapillaroscopy (NVC) is a diagnostic tool to evaluate micro-vasculature. Presence of choroidal vasculopathy is apparent in central serous chorioretinopathy (CSCR). Objectives: In this study, it was aimed to assess capillaroscopic findings of nailfold in patients with CSCR. To best of our knowledge, there is no study assessing NVC findings in CSCR in the literature. Methods: Sixty-one patients with CSCR who met inclusion criteria and 82 age- and sex-matched healthy controls were included to the study. A videocapillaroscopy device with 200x magnification was used for capillaroscopic assessment. Results: The mean age was 48.79 ± 11.146 years in the patient group (13 female, 48 male) whereas 49.38 ± 9.02 years in the control group (17 female, 65 male). The age and gender were comparable in the patient and control groups (p=0.727 and p=0.933, respectively). The capillary count was found to be decreased in the patient group compared to control group. No significant correlation was found between capillary count and choroidal thickness (p=0.551; r=-0.081). In the patient group, the frequencies of major capillaroscopic findings including capillary ectasia, aneurysm, micro-hemorrhage, avascular area, tortuosity, neo-formation, bizarre capillary, bushy capillary, meander capillary and extravasation were found to be increased in the patient group. However, no significant correlation was detected between capillaroscopic findings and disease type and presence of attacks. Conclusions: This is first study in which nailfold capillary assessment was performed in patients with CSCR and we detected major capillaroscopic changes. These findings suggest that CSCR can be systemic microvasculopathy. Further studies are needed to clarify the diagnostic and prognostic value of capillaroscopy in CSCR. Disclosure of Interest: None declared